PENYIMPANGAN NORMA SOSIAL DALAM SENI LUKIS REALIS KONTEMPORER - ABDURRAHMAN, Drs. Erfahmi, M.Sn., Yasrul Sami, S.Sn., M.Sn. (Universitas Negeri Padang, 2018)
The creation of this final work aims to visualize the lives of today's youth. This painting shows the occurrence of social deviations that are often carried out by teenagers in the community, such as smoking, sucking glue, brawls, bullying and so on. The method and process of the work used in the creation of this painting works through several stages: (1) Preparation, (2) Elaboration, (3) Synthesis, (4) Realization of the Concept, (5) Completion. The results of the visualization of the lives of adolescents today reveal the condition of adolescents who often violate norms in the community and can cause negative impacts on themselves and those around them, which are manifested in 10 paintings with the title: (1) Metropolitan, (2) Drinks , (3) Bullying, (4), Neglected (5) Sadness, (6) Fighting, (7) Stress, (8) Inhalen, (9) Cigarettes, (10) Bad.Kata kunci: penyimpangan norma sosial, remaja, seni lukis